2020
DOI: 10.21203/rs.3.rs-17585/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uganda’s Increasing Dependence On Development Partner’s Support For Immunization – A Five Year Resource Tracking Study (2012 – 2016)

Abstract: Background: In Uganda, there are persistent weaknesses in obtaining accurate, reliable and complete data on local and external investments in immunization to guide planning, financing, and resource mobilization. This study aimed to measure and describe the financial envelope for immunization from 2012 to 2016 and analyze expenditures at sub-national level.Methods: The Systems of Health Accounts (SHA) 2011 methodology was used to quantify and map the resource envelope for immunization. Data was collected at nat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Vaccination is one of the most successful cost-effective interventions for controlling vaccine-preventable diseases, thereby reducing childhood morbidity and mortality (Kamya et al, 2021). Although remarkable improvement has been made since 1974 when the World Health organization introduced the expanded program for immunization, access to vaccines still remains a challenge in many developing countries with the lowest improvements reported among disadvantaged and marginalized groups.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination is one of the most successful cost-effective interventions for controlling vaccine-preventable diseases, thereby reducing childhood morbidity and mortality (Kamya et al, 2021). Although remarkable improvement has been made since 1974 when the World Health organization introduced the expanded program for immunization, access to vaccines still remains a challenge in many developing countries with the lowest improvements reported among disadvantaged and marginalized groups.…”
Section: Introductionmentioning
confidence: 99%
“…Participants reported negotiating credit with local private transport companies including commercial motorcycle drivers, while awaiting the release of PHC funds for use as a refund. According to Ministry of Health EPI guidelines, the transportation of vaccines from the district vaccine store to lower health facilities is the mandate of the district health office which can be achieved if transport means and fuel is availed through PHC funds [22]. Our study revealed that this transportation of vaccines was affected due to lack of available transport facilities.…”
Section: Discussionmentioning
confidence: 83%